A IMPLANTAÇÃO DO PLANEJAMENTO ESTRATÉGICO EM ORGANIZAÇÕES COMPLEXAS: O CASO DA UNIVERSIDADE DO ESTADO DE SANTA CATARINA - Mariana Oliveira Moritz (Universidade Federal de Santa Catarina, 2012)
This article aims to describe how management practice, the implementation of strategic planning in a complex organization in the event the Plan 20, whose development and action occur at the Universidade do Estado de Santa Catarina (UDESC). The theoretical aspects of complexity sought to weave the university as an organization and processes covering strategic management and planning pertaining to it, giving views of the characterization UDESC and Plano 20. This research was a descriptive and qualitative perception culminated in the implementation of the action as a strategic tool of difficult internal membership, but who nevertheless motivates those who believe that this is the first step to making changes at the university.